The Impact of the Existence of APT Pranoto Airport on the Income of Taxi Drivers at Samarinda City Airport - Meilinia Safira, Bunga; Aziza Gaffar, Emmilya Umma (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This study aims to determine the impact of the existence of airports on the income of Samarinda airport taxi drivers. This type of research is qualitative descriptive. The data taken by the author is primary data and secondary data. Data collection techniques are in the form of observation, interviews, and documentation. The results of the study show that the existence of APT Pranoto Airport, which is characterized by many flight routes, complete facilities, and its location far from the city center, has a positive impact on the income of airport taxi drivers. However, there are other factors that also affect taxi driver income such as the number of airplane passengers, demand for airport taxis on holidays, differences in taxi fares, and competition with online transportation modes